2016
DOI: 10.4269/ajtmh.15-0799
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviruses and Rhinoviruses: Molecular Epidemiology of the Most Influenza-Like Illness Associated Viruses in Senegal

Abstract: Abstract. Different viruses have been identified as etiologic agents of respiratory tract infections, including severe cases. Among these, human rhinoviruses (HRVs) and human enteroviruses (HEVs) are recognized as leading causes. The present study describes the molecular epidemiology of HRVs and HEVs in Senegal over a 3-year surveillance period. From January 2012 to December 2014, nasopharyngeal and oropharyngeal swabs specimen were collected from patients with influenza-like illness (ILI). A real-time reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
2
11
1
Order By: Relevance
“…This high circulation of picornaviruses in children was clearly reflected in the data collected after many years of surveillance of these viruses in people in Senegal [9]. Interestingly, in the present pediatric study about 59.7% of picornaviruses infection cases are related to low respiratory tract infections (LRTIs) although these viruses are usually related to mild URTI.…”
Section: Authors' Contributionsmentioning
confidence: 71%
See 1 more Smart Citation
“…This high circulation of picornaviruses in children was clearly reflected in the data collected after many years of surveillance of these viruses in people in Senegal [9]. Interestingly, in the present pediatric study about 59.7% of picornaviruses infection cases are related to low respiratory tract infections (LRTIs) although these viruses are usually related to mild URTI.…”
Section: Authors' Contributionsmentioning
confidence: 71%
“…The most common viruses associated with influenza-like illness (ILI) in patients were influenza viruses, adenoviruses (ADVs), human rhinoviruses (HRVs), respiratory syncytial virus (RSV), enteroviruses (EVs), parainfluenza viruses (PIVs), human metapneumovirus (hMPV), and human coronaviruses (HCoVs) 229E, OC43, NL63, and HKU1. Studies focused on HRV and RSV, have revealed a high activity of both viruses in children under 5 in Senegal, especially during the rainy season [9,10]. Indeed, previous studies have well established that RSV is the leading cause of lower respiratory tract infections (LRTIs) in young children with 50% of children infected during their first year of life, and 100% having experienced at least one infection by 3 years of age [11].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we hypothesize that our high EV prevalence is further explained by our relatively young population. While other studies often focus on a broader age group, EV’s are more prevalent in young age groups, when compared to older children and adults [ 15 , 19 ]. Thirdly, the inclusion criteria of the SevAna study led to a higher number of participants included during the rainy season, in which malaria, a well-known cause of anemia, is highly prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Viruses most commonly found in Senegal were respiratory syncytial virus (RSV ), adenovirus, rhinovirus, influenza virus A, enterovirus, human bocavirus, and parainfluenza viruses. 16 Furthermore, there are indications that nowadays ARTIs are more often caused by the sequential or concurrent interaction of different pathogens and that the presence of multiple organisms is linked with the existence of a LRTI and with severity of disease. 17,18 To reduce paediatric mortality caused by LRTI, while fighting antibiotic resistance, more knowledge about the cause of respiratory infections, especially in low-and middle-income countries, is essential.…”
Section: Pathogens Causing Respiratory Tract Infections In Children Lmentioning
confidence: 99%